Development of New Multilayer Active Packaging Films with Controlled Release Property Based on Polypropylene/Poly(Vinyl Alcohol)/Polypropylene Incorporated with Tea Polyphenols. Issue 7 (17th June 2019) - Chen, Chenwei; Li, Chenxi; Yang, Shaohua; Zhang, Qinjun; Yang, Fuxin; Tang, Zhipeng; Xie, Jing
Abstract : Abstract: The polypropylene/poly(vinyl alcohol)/polypropylene (PP/PVA/PP) multilayer active films with controlled release property were developed, of which the intermediate PVA layer was incorporated with 4% (w/w) tea polyphenols (TP) and the microporous PP films with different pore size were used as the internal controlled release layer. The SEM results showed that each layer of these films was agglutinated tightly. With increasing pore size from 171.05 to 684.03 µm, there were little effect on the films' color and opacity, the tensile strength (TS) and elongation at break (EAB) decreased slightly, the gas barrier (O2 and water vapor) property of the film reduced faintly, the time of achieving the release equilibrium in 50% ethanol decreased from 75 hours to 30 hours. The diffusion coefficient for the films increased with the increase of pore size, from 2.06 × 10 −11 cm 2 /s to 8.06 × 10 −11 cm 2 /s, suggesting that the release rate of TP increased as the pore size increased. The results were indicated that its release rate could be controlled by adjusting the size of pore. The films also exhibited different antioxidant activities due to their different release profiles of TP. It showed promise for developing the controlled release active packaging film based on this concept. Practical Application: Controlled release packaging is propitious to extension of food shelf life. The microporous polypropylene films with different pore size used as the internal layer of polypropylene/poly(vinyl alcohol)/polypropylene (PP/PVA/PP) multilayer active films was proved that the release rate of tea polyphenols in the intermediate PVA layer released from the films into the food simulant can be controlled by adjusting the size of pore in this study. It showed a good prospect for using microporous or perforation‐mediated film as the internal layer of multilayer film to develop the controlled release active packaging film for food packaging.